The hierarchical flower-like MoS2 nanosheets incorporated into PES mixed matrix membranes for enhanced separation performance. (October 2020) - Wang, Xiaoping; Wu, Chao; Zhu, Tongren; Li, Pan; Xia, Shengji
Abstract: Membrane fouling is an issue of concern due to the hydrophobic properties of polyethersulfone (PES) membrane when applied in water treatment. In this work, a facile hydrothermal method was utilized to synthesize hierarchical flower-like structured molybdenum disulfide nanosheets (HF–MoS2 NSs) that then incorporated into PES membranes as composite membranes. We characterized their permeability, the separation performance, the antifouling performance, and the antibacterial activity systematically. Results showed that composite membranes exhibited a better pure water flux (286 LMH/bar) at the HF–MoS2 NSs content of 0.4 wt%, which was 1.8 times higher than the control membrane. Also, composite PES membranes achieved 98.2% and 96.9% rejection of BSA and HA in comparison with the control PES membrane (87.3%, and 84.5%, respectively). Compare to the control PES membrane, the flux recovery ratio of the composite membrane increased from 69% to 88% for BSA fouling and increased from 84% to 93% for HA fouling. The retention rate for the organic dyes also improved slightly after HF–MoS2 NSs incorporation into the membrane. Additionally, the composite membranes exhibited a relatively high antibacterial activity against E. coli and B. subtilis with antibacterial rates of 67.8% and 82.5%, respectively. In conclusion, HF–MoS2 NSs incorporated composite membranes were shown to have outstanding filtration performance and could be a promising candidate for practical application in water filtration. Graphical abstract: Image 1 Highlights: HF–MoS2 NSs synthesized by the simple hydrothermal method. HF–MoS2 NSs first introduced into the PES casting solution. The fabricated composite membranes exhibited 1.8 times higher water flux. The antifouling and antibacterial properties of MoS2 /PES membranes were enhanced.